Development of Waginem (Morning and Evening Time) Mathematics Teaching Aids for Time Materials - A Afriyani; Norma Dewi Shalikhah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This research is motivated by the lack of teaching aids for time material at school. Thepurpose of this study was to develop Waginem (Morning and Evening Time) teaching aidsto make it easier for students to understand the time material in learning mathematics.The type of research is development research (R&D) which consists of several stages,namely finding potentials and problems, gathering information, product design, designvalidation, design improvement, and product testing. The product trial subjects werestudents of class II MI Muhammadiyah Paremono Magelang. The instrument used is aquestionnaire sheet to determine the validity and responses of students to teaching aids.The results showed that Waginem's teaching aid was very valid with a score of 89.5% andstudent responses scored 97.2% with very good criteria. So that the conclusion is thatWaginem's teaching aids are suitable for use in time material learning mathematics forgrade II elementary school students.